Gestational exposure to polybrominated diphenyl ethers and social skills and problem behaviors in adolescents: The HOME study. (15th January 2022) - Hartley, Kim; MacDougall, Melinda C.; Terrizzi, Brandon; Xu, Yingying; Cecil, Kim M.; Chen, Aimin; Braun, Joseph M.; Lanphear, Bruce P.; Newman, Nicholas C.; Vuong, Ann M.; Sjödin, Andreas; Yolton, Kimberly
Graphical abstract: Highlights: We examined associations between gestational PBDE exposure and outcomes at age 12. Outcomes included self- and caregiver-reported social skills and problem behaviors. Gestational PBDE exposure was associated with poorer outcomes in adolescent males. No associations were noted among female participants. Abstract: Background: Polybrominated diphenyl ethers (PBDEs) are persistent environmental pollutants used as flame retardants. Gestational PBDE exposure has been associated with a variety of behavior problems in children, but little is known about its impact into adolescence, particularly on social skills, which are important for achieving social competence, establishing identity, and forming lasting relationships. Objective: We investigated associations between gestational exposure to PBDEs and social skills and problem behaviors in early adolescence in a longitudinal pregnancy and birth cohort in Cincinnati, Ohio (recruited 2003–2006). Methods: We measured maternal serum concentrations of five PBDE congeners during gestation. At age 12, we measured social skills and problem behaviors scores for 243 adolescents using self- and caregiver-report on the Social Skills Improvement System (SSiS). We used multivariable linear regression models to estimate associations between maternal PBDE concentrations and SSiS scores, controlling for potential covariates. We report associations for the five congeners and a summary exposure variable (∑5 BDE: the sum of BDE- 28, 47, 99, 100, and 153, n = 197). Results: We found sex-specific associations of ∑5 BDE concentrations with adolescent-reported Problem Behaviors (∑5 BDE × sex pint = 0.02) and caregiver-reported Social Skills (∑5 BDE × sex pint = 0.02). In sex-stratified models, log10 transformed data revealed increased maternal ∑5 BDE concentration among males was associated with decreased caregiver-reported Social Skills composite score (β = -10.2, 95% CI: −19.5, −1.0), increased adolescent-reported Problem Behaviors composite score (β = 12.1, 95% CI: 5.4, 18.8), and increased caregiver-reported Problem Behaviors composite score (β = 6.2, 95% CI: 0.7, 11.7). Further analysis on SSiS subscales revealed similar patterns in significant associations among males. There were no statistically significant associations in stratified models among females despite higher ∑5 BDE exposure (Female GM=40.15 ng/g lipid, GSE=1.10; Male GM=35.30 ng/g lipid, GSE=1.09). Discussion: We found gestational PBDE exposure in males was associated with poorer behavioral outcomes, extending previous findings among this cohort into early adolescence.